Trapa natans Husk‐Derived Nanoporous Carbons as Electrode Materials for Sustainable High‐Power Microbial Fuel Cell Supercapacitor Systems. Issue 5 (15th December 2021) - Hsu, Chia-Chieh; Lin, Yi-Chu; Lin, Yao-Yu; Li, Hsin-Tien; Ni, Chung-Sheng; Liu, Chao-I; Chang, Chao-Chin; Lin, Liang-Chen; Pan, Yung-Tin; Liu, Shih-Fu; Liu, Tzu-Yin; Chen, Han-Yi
Abstract : Microbial fuel cells (MFCs), which convert chemical energy into electricity using microbes, are an emerging sustainable energy technology. However, high costs and low power output limit the advanced development of MFCs. This study utilizes the agricultural waste, Trapa natans husks, to obtain low‐cost nanoporous carbons. The Trapa natans husk‐derived nanoporous carbons (TNHs) are used as electrode materials in Escherichia coli system‐based MFCs. After optimization of both anode and cathode materials for MFCs, a high average power density of 5713 mW m −2 is achieved, which is 1.9 times greater than that of commercial activated carbon. It is shown that TNHs have better bacterial adhesion and electrochemical activities owing to their favorable pore size distribution, suitable functional group, high surface area, and excellent biocompatibility and conductivity. Furthermore, the supercapacitors (SCs) with TNH‐based electrodes are utilized to store the energy generated from MFCs. The SC with TNH‐600 electrodes exhibits a high specific capacitance of 84 F g −1 at a current density of 1 A g −1 after 1000 cycles. This study demonstrates that TNH is a promising electrode material for biofriendly and renewable MFCs, and the MFC‐SC system with TNH electrodes is a high‐power sustainable energy generation and storage device. Abstract : A Trapa natans husks‐derived electrode material (TNH) is used in microbial fuel cells (MFCs) with a high average power density of 5713 mW m −2 . Moreover, supercapacitors (SCs) with TNH‐based electrodes are used as energy storage from MFCs, exhibiting a high specific capacitance of 85 F g −1 after 1000 cycles. It is shown that TNH is a promising material in MFC‐SC system.